2010
DOI: 10.1159/000231984
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant MicroRNA-155 Expression Is an Early Event in the Multistep Progression of Pancreatic Adenocarcinoma

Abstract: Background/Aims: Pancreatic intraepithelial neoplasia (PanIN) is the most common noninvasive precursor to invasive pancreatic adenocarcinoma. Misexpression of microRNAs (miRNAs) is commonly encountered in invasive neoplasia; however, miRNA abnormalities in PanIN lesions have not been documented. Methods: Three candidate miRNAs (miR-21, miR-155, and miR-221) previously reported as overexpressed in pancreatic cancers were assessed in 31 microdissected PanINs (14 PanIN-1, 9 PanIN-2, 8 PanIN-3) using quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 53 publications
(75 reference statements)
3
89
0
1
Order By: Relevance
“…[6][7][8][9] Sustained proliferation is a hallmark of transformed cells. Knockdown of BIC in malignant MyLa2059 cells entailed a 40% decrease of miR-155 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] Sustained proliferation is a hallmark of transformed cells. Knockdown of BIC in malignant MyLa2059 cells entailed a 40% decrease of miR-155 expression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found overexpressed in hematological 4,5 as well as a number of solid cancers. [6][7][8][9] miR-155 is localized within an exon of its precursor gene BIC (B cell integration cluster or pri-miR-155). 4 Transiently elevated expression of miR-155 plays a role in the activation of several types of immune cells, 2,[10][11][12] whereas constitutively high levels of this miRNA can result in the development of malignancies by increase of genomic instability 13,14 and sustained proliferation and survival 5,15 of malignant cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on miRNA expression profiling of pancreatic adenocarcinoma. Aberrant expression of miRNA, such as miR-21 and miR-155, in the pancreas, often contributes to cancer development and invasion (Giovannetti et al, 2010;Ryu et al, 2010). On the other hand, miRNA such as miR-34 and miR-150 may also suppress the growth and malignant behavior of pancreatic cancer cells (Liu et al, 2011;Srivastava et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…miR-155 plays an important role in various physiological and pathological processes (Faraoni et al, 2009;Elton et al, 2012) and has been found to be upregulated in several solid tumors, such as clear-cell kidney cancer (Juan et al, 2010), hepatocellular carcinoma (Wang et al, 2009a), breast cancer (Jiang et al, 2010;Kong et al, 2010), pancreatic cancer (Habbe et al, 2009;Greither et al, 2010;Ryu et al, 2010), and lung cancer (Yanaihara et al, 2006;Donnem et al, 2011). Moreover, high miR-155 expression is associated with a poor prognosis in lung cancer (Yanaihara et al, 2006;Donnem et al, 2011), suggesting that elevated miR-155 expression might be a prognostic biomarker of lung cancer (Xie et al, 2010).…”
Section: Discussionmentioning
confidence: 99%